Ice cream phase composition study using low temperature 1H NMR spectroscopy - Polishchuk, Galyna; Ivanov, Sergey; Krupskaya, Tatyana; Turov, Vladimir (My University, 2013)
The results of undertaken studies can be used to calculate the actual sucrose and lactose concentrations in mixtures and ice cream through a wide range of low temperatures.
Keywords: ice cream; phase composition; bound water; кафедра технології молока і молочних продуктів; морозиво; зв'язана вода; фазовий склад; мороженное; фазовый состав; связанная вода